Use of 99mTc 2‐methoxyisobutyl isonitrile in minimally invasive radioguided surgery in patients with primary hyperparathyroidism: A narrative review of the current literature. Issue 2 (4th June 2013) - Denmeade, Kristie A.; Constable, Chris; Reed, Warren M.
Abstract The use of technetium‐99m 2‐methoxyisobutyl isonitrile (99mTc MIBI) for assistance in minimally invasive radioguided surgery (MIRS) is growing in popularity as a safe, effective, and proficient technique used for parathyroidectomy in primary hyperparathyroidism (PHPT) treatment. Previously, the preferred treatment for PHPT was bilateral neck exploration (BNE), a very invasive, costly, and lengthy procedure. However, as a large majority (80–85% of cases of PHPT) are attributed to a single parathyroid adenoma (PA), a simpler more direct technique such as MIRS is a far better option. The following article is an exploration of the current literature concerning varied protocols utilizing 99mTc MIBI for assistance in MIRS for patients undergoing treatment of PHPT. This technique boasts many advantageous outcomes for patients suffering from PHPT. These include a reduction in cost, operating time, and patient recovery; less evidence of post‐surgical hypocalcaemia, less pain, and complications; superior cosmetic results; same‐day discharge; and the possibility of local anaesthesia which is particularly beneficial in elderly patients. Better outcomes for patients with deep or ectopic PAs, reduced intra‐operative complications, and improved cosmetic outcomes for patients who have previously undergone thyroid and/or parathyroid surgery are also advantageous. Of the literature reviewed it was also found that no patients suffered any major surgical complications such as laryngeal nerve palsy or permanent hypoparathyroidism using 99mTc MIBI for assistance in MIRS.